2017
DOI: 10.1021/acsami.7b09240
|View full text |Cite
|
Sign up to set email alerts
|

Significant Enhancement of Thermal Conductivity in Nanofibrillated Cellulose Films with Low Mass Fraction of Nanodiamond

Abstract: High thermal conductive nanofibrillated cellulose (NFC) hybrid films based on nanodiamond (ND) were fabricated by a facile vacuum filtration technique. In this issue, the thermal conductivity (TC) on the in-plane direction of the NFC/ND hybrid film had a significant enhancement of 775.2% at a comparatively low ND content (0.5 wt %). The NFC not only helps ND to disperse in the aqueous medium stably but also plays a positive role in the formation of the hierarchical structure. ND could form a thermal conductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 61 publications
6
82
0
Order By: Relevance
“…Although NDs are not free from the classical size effect, NDs should inherit the superior property of bulk diamond to a degree [103]. In 2017, Song et al reported that addition of ND particles to CNF films enhances thermal conductivity of the films efficiently [104]. Among the variety of NDs, ND materials prepared by detonation synthesis are distinguished from others by a moderate production cost and commercial availability.…”
Section: Nanocelluloses As Composite Scaffoldsmentioning
confidence: 99%
“…Although NDs are not free from the classical size effect, NDs should inherit the superior property of bulk diamond to a degree [103]. In 2017, Song et al reported that addition of ND particles to CNF films enhances thermal conductivity of the films efficiently [104]. Among the variety of NDs, ND materials prepared by detonation synthesis are distinguished from others by a moderate production cost and commercial availability.…”
Section: Nanocelluloses As Composite Scaffoldsmentioning
confidence: 99%
“…This may be because a nanodiamond is more expensive and is electrically nonconductive in its pristine state. In composites with nanofibrillated cellulose (Figure 4b), a nanodiamond was used for constructing highly thermally conductive, mechanically resistant and optically transparent films with potential application as lateral heat spreaders for portable electronic equipment [70]. A highly mechanically resistant and optically transparent nanopaper was made of cationic CNFs and anionic nanodiamond particles by filtration from a hydrocolloid and subsequent drying [159].…”
Section: Preparation and (Bio)application Of Nanocellulose/nanodiamonmentioning
confidence: 99%
“…In addition to its advantageous combination with nanocarbon materials, nanocellulose is an appealing material for biomedical applications due to its tunable chemical fluorescence and luminescence [26,71,72] photothermal activity [56], hydrolytic stability [61], nanoporous character and high adsorption capacity [49,61]. Nanocellulose/nanocarbon composites can therefore be used in a wide range of industrial and technological applications, such as water purification [22,29,43,49,54,56,61,[73][74][75][76], the isolation and separation of various molecules [22,74,[77][78][79], energy generation, storage and conversion [21,23,44,47,64,[80][81][82][83][84][85], biocatalysis [86], food packaging [67][68][69]87], construction of fire retardants [48], heat spreaders [70] and shape memory devices [38,[88][89][90]. These comp...…”
Section: Introductionmentioning
confidence: 99%
“…Natural diamond possesses a supremely large modulus (1 TPa) and the highest thermal conductivity (2200 W/(m K)) among all the elemental substances. Therefore, ND is accepted as a mechanical-and thermal-reinforcement filler in composites owing to their large modulus and thermal stability [28,36,37,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we focused on the cellulose nanofiber composites with chemically nanofiberized celluloses as matrixes and ND as fillers for mechanical reinforcement and thermal conductive enhancement, and therefore, investigated their mechanical properties and thermal conductivities [35,40]. The effects of GO fillers on the mechanical and thermal properties of the cellulose nanofiber composites were also evaluated and compared with the results of the ND loading.…”
Section: Introductionmentioning
confidence: 99%